Planning Services for Sludge Treatment Installation (IPLT) Nganjuk Regency - E Rosydah; E N Hidayah (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
Abstract. Nganjuk Regency is one of the regencies in East Java Province with a fairly high population of 1,103,491 people. The high population affects the rate of wastewater production in a Regency/City. The purpose of this study is to plan the installation of a sewage treatment plant (IPLT) and the services that will be applied to the IPLT. This research method uses data analysis methods. Based on the septic tank users and the service distance of the 100% serviced area selected for the priority zone served by 5 sub-districts, namely Nganjuk District, Rejoso District, Sukomoro District, Loceret District, Bagor District, because these districts are the closest to the planning area. The toilet suction pattern that will be applied is the direct transportation pattern and the collective transportation